FIRST SINGLE-CENTER EXPERIENCE WITH LUSPATERCEPT THERAPY IN LOW-RISK MYELODYSPLASTIC SYNDROME (LR-MDS) PATIENTS WITH TRANSFUSION DEPENDENCE REFRACTORY TO ERYTHROPOIETIN THERAPY - A. Jonasova; L. Minarik (Leukemia Research Reports, 2024)
Introduction: Luspatercept is a recent breakthrough in the therapy of anemia in low-risk MDS. Methods: From January 2021 to October 2023, 44 patients (median age 77, M/F 25/19, WHO 2016 classification: MDS-RS-MLD 28, MDS-MLD -4, RARS-T 8, CMML- 0 2, 5q- + RS 2, IPSS-R: very low 2, low 33, Intermediate 9, IPSS-M (35 pts): very low + low 18, moderate low 11, moderate high 2, high 2, very high 2) were treated with luspatercept. Median follow-up was 13 months (range 1-42). The median number of cycles was 15 (2-42). Transfusion dependency (TD) before luspatercept initiation ranged from 2 transfusion units (TU) to 12 TU/8 weeks. All patients were tested for SF3B1 mutation. Results: We evaluated 42 patients. Twenty-four (57 %) patients reached TI (>12weekes), 6 (14 %) patients have had a reduction in transfusion need (HI, according to IWG criteria 2006). There were differences in response according to transfusion burden. Significant more responders belonged to lower IPSS-R, IPSS-M categories. In 17 patients, we added ESA (± prednisone), which led to the improvement of response in 12 cases with 9 TI. Four patients died (2-disease progression, 2 for comorbidity). There were no adverse effects of Grade II or more. Conclusions: We did observed better responses in patients bearing single mutation in SF3B1, in lower IPSS-R and IPSS-M risk categories, patients with LTB and lower initial baseline EPO levels. The higher response rate in our follow-up may be influenced by the combination with ESA and rapid dose escalation.